THE BIOHARMONIZED RECONNECTION OF THE AGRICULTURAL SYSTEM IN ROMANIA'S TERRITORY IN THE PROCESS OF ADMINISTRATIVE REORGANIZATION - Romulus GRUIA; Agatha POPESCU; Liviu GACEU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Territorial reorganization is a concern at the European level and of the component states in order to adapt to the requirements of contemporary society. Romania is an eloquent example in this sense because of the major imbalances of all kinds which have been accumulated between Romania's counties based on an outdated model of territorial organization having serious socio-economic and political implications. In this context, the paper aimed to find a performant, optimized and balanced solution through a new approach based on the principles of the concept of "societal bioharmonisation". A conceptual and methodological mechanism is described which is based on the evolution of the development in the convergence with natural resources (relief, waters, forests, land categories) with food territorial security through production and agri-food potential, based on human and financial resources, with the quality of life and (through purchasing power and life expectancy) of the local community. The research methodology included: bibliographic study, data collection and processing using different procedures like: multi-criterion analysis, pointing method, weighting method, the weighted arithmetic mean, comparisons among the extreme regions etc. A series of calculation formulas were used to quantify through the necessary objective indicators and to reorganize the territory from 41 counties with huge gaps among them at present to 11 balanced departments and the capital separately as shown in the proposed new Model of territorial administrative balanced and bio-harmonized organization. The offered solution shows that by harmonizing the factors taken into account in terms of agriculture and food (for example: weighted arithmetic mean etc) a level of bio-harmonization of the administrative-territorial structures of Romania is reached with the potential integration, efficiency and balance, thus reducing the differences in the economic development and life quality. A significant decrease of the polarization of the society development and improved life quality is assured by the new Model so that the difference among the territorial units was diminished from +/- 110 % to a much smaller difference of +/- 14 %, without taking into consideration Bucharest which operates like a metropolis. In this way, the new administrative organization induces through the proposed model an optimized utilization of the resources and a greater equity by bringing closer the opportunities offered to the population throughout the country.